Arthrodesis of the equine proximal interphalangeal joint: a biomechanical comparison of 2 different LCP systems - Vidović, Aleksandar; Jansen, Dorothea; Schwan, Stefan; Goldstein, Alexander; Ludtka, Christopher; Brehm, Walter (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2020)
Objective This study compares the mechanical stability and surgical usability of 2 locking plate systems (Kyon ALPS-20 and Synthes PIP-LCP system) for arthrodesis of the equine proximal interphalangeal joint (PIJ).Material and methods The experimental ex vivo study included 6 pairs of cadaver distal limbs (n = 12). All specimens were derived from Warmblood horses of various ages that were euthanized for non-orthopedic reasons. Of the 12 limbs collected, 3 left and 3 right distal limb specimens were randomly assigned to each system for implantation. Two abaxial 4.5-mm cortical screws were inserted transarticularly in all cases. Both systems were implanted according to the manufacturer’s instructions with the plates placed centrally between the 2 transarticular screws. The ALPS-20 systems were implanted using Kyon B-6.4-mm monocortical locking screws in all positions. The LCP systems were implanted axially using 2 Synthes 5-mm locking screws in the proximal and distal positions, with a standard 4.5-mm cortical screw inserted in the middle position. All constructs underwent CT-scans after implantation and biomechanical testing to detect implant deformation. Uniaxial mechanical loading was applied via a servo-hydraulic test system at a test speed of 50 mm/s, up to a maximum displacement of 80 mm. The resulting load-displacement curves were used to calculate yield point, stiffness, and maximum force for each construct. The measured values were evaluated for statistical significance (p < 0.05) between the 2 plate systems via one-factor ANOVA (Tukey test). The statistical power was verified for yield force, stiffness, and maximum load.Results No statistically significant differences between the 2 preparation groups were calculated across all of the measured parameters (p > 0.05). The ALPS system implants showed no signs of deformation, either in the plates or the screws. In contrast, the LCP demonstrated visible deformation, which had already occurred at the time of implantation from the tightening of the middle screw, as well as during the subsequent testing of the implants. After biomechanical testing, deformations ranging between 3.1° and 7.0° were measured in 4 LCPs. A total implant failure was observed for 2 LCPs.Conclusion and clinical relevance Both systems demonstrated comparable mechanical properties in the present study’s ex vivo test model for equine PIJ arthrodesis. As such, the Kyon ALPS-20 may be a good alternative to the Synthes LCP for equine PIJ arthrodesis.
Keywords: Horse; PIP joint; PIP joint fusion; osteosynthesis; PIP plate; ALPS